LA HERNIOPLASTIA INGUINAL EN EL 2012. ENCUESTA A CIRUJANOS DE LA ASOCIACIÓN ARGENTINA DE CIRUGÍA (Revista Argentina de Cirugía, 2022)
Background: Inguinal hernia repair has experienced two important changes in the last decades which have gained different acceptance amongst general surgeons: the tension-free techniques with polypropylene meshes and the laparoscopic approach of the repair.In this study we investigated the actual view on the subject in our country amongst the members of the Argentine Association of Surgery (AAC), focusing the survey in the learning of the techniques and the obstacles for its employment related to cost and availability of supplies and equipment, to assess its current indications and the benefits of encouraging its development in the present times. Objective: To analyze the results of a questionnaire performed amongst members of the AAC, regarding the use of polypropylene mesh and the laparoscopic approach in inguinal hernia repair.Population: 559 surgeons, members of the AAC.Methods:Aquestionnaire was sent by mail to all members of the AAC regarding their indications and frequency of use of a polypropylene mesh and the laparoscopic approach for the treatment of inguinal hernia in the last 3 years, also inquiring about the reasons for not having employed them. The questionnaire was sent again two months later to attain a larger response rate. Some data were crossed amongst the items of the questionnaire to obtain new data emerging from their combination.
Keywords: inguinal hernia; surgery; survey; Argentina